2020
DOI: 10.1029/2019jd031564
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Elastic Scattering on Electron Swarm Distribution in Electrified Gases

Abstract: The propagation of energetic electrons through air is one key component in the generation of high-energy atmospheric phenomena such as lightning-generated X-ray bursts, terrestrial gamma ray flashes (TGFs), and gamma ray glows. We show here that models for this propagation can be considerably affected by the parameterization of the differential cross section of elastic scattering of electrons on the molecular components of air. We assess existing parameterizations and propose a more accurate one that builds up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Ideally one may use the knowledge of a differential cross section (DCS) to determine at what angle an electron is likely to scatter from the target given its incident energy; however, this is often easier said than done due to the computational cost of relating a random number to cross section data (the inverse problem and interpolation procedures), as well as the lack of comprehensive DCS data available from the literature or databases. Several analytic forms of an electron-neutral elastic scattering angular distribution function exist in the literature [1,[15][16][17][18][19], and we note the particular long-term persistence of an empirical formula first proposed by Surendra et al [1] (later shown to be derived from the inelastic dipole Born approximation [17]), which appears to have become a de facto standard for many MC collision methods to this day.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Ideally one may use the knowledge of a differential cross section (DCS) to determine at what angle an electron is likely to scatter from the target given its incident energy; however, this is often easier said than done due to the computational cost of relating a random number to cross section data (the inverse problem and interpolation procedures), as well as the lack of comprehensive DCS data available from the literature or databases. Several analytic forms of an electron-neutral elastic scattering angular distribution function exist in the literature [1,[15][16][17][18][19], and we note the particular long-term persistence of an empirical formula first proposed by Surendra et al [1] (later shown to be derived from the inelastic dipole Born approximation [17]), which appears to have become a de facto standard for many MC collision methods to this day.…”
Section: Introductionmentioning
confidence: 72%
“…Since the adoption of MC collision treatments for simulating electron collisions in particle based models, a significant number of models that describe angular distributions of elastic electron-neutral scattering have been formulated and employed in codes. Thoughtful reviews of this topic can be found in the works of Moss et al [6], Schmalzried and Luque [18], and Janssen et al [17], where a range of popular options used throughout the plasma modeling community were compiled and analyzed. As discussed in the introduction, a common theme to many of these models is that near-isotropic or backward scattering scenarios are rarely modeled accurately.…”
Section: Common Elastic Scattering Angular Distribution Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A truncated series of LPs P l in cos χ is added to the FSR to fit the experimental DCS [23] in order to characterize the large angle or back scattering:…”
Section: Methods Consisting Of Both Elastic and CX Collisionsmentioning
confidence: 99%
“…The second reason is the lack of analytically simpleto-use models of DCS, through which scattering angles can be randomly sampled by easy inversion instead of the timeconsuming accept-reject method. During the last two decades, different angular scattering models have been compared in various scenarios, such as electron transport study, ionization source terms in glow discharge, thermal runaway electrons in streamer discharge, and interstellar neutral atoms in the outer heliosheath [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. It was found that the angular scattering model is a non-trivial topic.…”
Section: Introductionmentioning
confidence: 99%